Amanda wakes up [large type] - Camerota, Alisyn (Wheeler Publishing, a part of Gale, Cengage Company, 2017)
When Amanda Gallo, fresh from the backwater of local TV, lands the coveted morning anchor slot at FAIR News, she's finally made it: a six-figure salary, wardrobe allowance, plenty of on-air face time, and a chance to realize her dreams, not to mention buy herself lunch. But she finds her journalistic ideals shredded as she struggles to keep up with the issues in a ratings-crazed madhouse: battling for hair and makeup time; coping with her sexist (but scathingly handsome) coanchor, Rob; mixing up the headlines with pajama modeling on the street, and showing Benji Diggs, her media maestro boss, that she's got what it takes. When a wild-card candidate, former Hollywood actor Victor Fluke, appears on the election scene, Amanda must decide what she needs to hold on to in order to save herself.